If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -3)(4x + 1) = 0 Reorder the terms: 3(-3 + 2x)(4x + 1) = 0 Reorder the terms: 3(-3 + 2x)(1 + 4x) = 0 Multiply (-3 + 2x) * (1 + 4x) 3(-3(1 + 4x) + 2x * (1 + 4x)) = 0 3((1 * -3 + 4x * -3) + 2x * (1 + 4x)) = 0 3((-3 + -12x) + 2x * (1 + 4x)) = 0 3(-3 + -12x + (1 * 2x + 4x * 2x)) = 0 3(-3 + -12x + (2x + 8x2)) = 0 Combine like terms: -12x + 2x = -10x 3(-3 + -10x + 8x2) = 0 (-3 * 3 + -10x * 3 + 8x2 * 3) = 0 (-9 + -30x + 24x2) = 0 Solving -9 + -30x + 24x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-3 + -10x + 8x2) = 0 Factor a trinomial. 3((-1 + -4x)(3 + -2x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-1 + -4x)' equal to zero and attempt to solve: Simplifying -1 + -4x = 0 Solving -1 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -4x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -4x = 0 + 1 -4x = 0 + 1 Combine like terms: 0 + 1 = 1 -4x = 1 Divide each side by '-4'. x = -0.25 Simplifying x = -0.25Subproblem 2
Set the factor '(3 + -2x)' equal to zero and attempt to solve: Simplifying 3 + -2x = 0 Solving 3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 0 + -3 -2x = 0 + -3 Combine like terms: 0 + -3 = -3 -2x = -3 Divide each side by '-2'. x = 1.5 Simplifying x = 1.5Solution
x = {-0.25, 1.5}
| -200=-8(3m+7) | | -5.2m+11.15=-3.41 | | -12=-z+12 | | 3(-6n+7)-2= | | 2+3x=5x+2 | | 1800-279x=3450 | | 23x+2y=164 | | y=2x+52 | | 119=-3(1+5k)+2 | | (x)(3x)=75 | | 14x+8=x^2 | | x+13=x+1 | | -9d-5+8+7d= | | -5x^2=-160 | | f(x)=-12x+8 | | 2(4a-1)=3(a+2) | | 9-13x-5-2x=7 | | 3x^3-25x^2+53x-15=0 | | 279x+1800=3450 | | -138=6(1-6x) | | 11x=2x^2-6 | | N=14+5q | | 6(5x-3)=102 | | 12x+9y=9y | | 3b-8(2b-3)=102 | | 9-c^2= | | 2x^2=756 | | 10x-7=91-4x | | 3x+-1=-32 | | 3(-4-9n)-6n= | | 84=6(2-x)-3x | | -2=-2(n-8) |